A PROPOSAL OF CUT ORDER PLANNING SOLUTION BASED ON MS EXCEL SOFTWARE FOR TEACHING PURPOSES - Tri, Nguyen Huu; Dao, Tran Thi Anh; Hong, Do Thi Thu; Loc, Truong Thi Xuan; My, Nguyen Thi Cam (HUIT Journal of Science, 2023)
This study creates an application based on Excel software which proposes appropriate cut order planning from industry garment orders. The implementation process includes starting the application, confirming how many garment sizes, how many fabric colors, and then declaring parameters of the order to consider the cut order planning in the fastest time. The application also supports the preparation of documents/reports for the cut order planning, calculates the fabric consumption and creates statistics reports of the cutting table data. The application was tested on two groups of students from the Faculty of Garment Technology and Fashion (Ho Chi Minh City University of Food Industry), with each group consisting of 112 students. The results show that the application can optimize timing, marker making, cut table and manpower and can be a powerful tool applied to courses for students of the Textile and Garment Faculty, in comparison to manual planning. It is also an effective cut order planning data storage solution in the Garment industry.